2017
DOI: 10.1002/2017gl073421
|View full text |Cite
|
Sign up to set email alerts
|

A planetary‐scale disturbance in the most intense Jovian atmospheric jet from JunoCam and ground‐based observations

Abstract: We describe a huge planetary‐scale disturbance in the highest‐speed Jovian jet at latitude 23.5°N that was first observed in October 2016 during the Juno perijove‐2 approach. An extraordinary outburst of four plumes was involved in the disturbance development. They were located in the range of planetographic latitudes from 22.2° to 23.0°N and moved faster than the jet peak with eastward velocities in the range 155 to 175 m s−1. In the wake of the plumes, a turbulent pattern of bright and dark spots (wave numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…This corresponds to the evolution of an eruption in the NTB in 2012 close to solar conjunction that could not be observed properly. A similar phenomena was observed in 2007 (Sánchez-Lavega et al 2008) and 2017 (Sánchez-Lavega et al 2017).…”
Section: Jupitersupporting
confidence: 84%
See 1 more Smart Citation
“…This corresponds to the evolution of an eruption in the NTB in 2012 close to solar conjunction that could not be observed properly. A similar phenomena was observed in 2007 (Sánchez-Lavega et al 2008) and 2017 (Sánchez-Lavega et al 2017).…”
Section: Jupitersupporting
confidence: 84%
“…First channel (visible; VIS) covers wavelengths below 1 µm and the second channel (short-wave infrared; SWIR) works above this value and up to 1.7 µm. PlanetCam images have been used so far for several works on Jupiter (Hueso et al 2017b;Sánchez-Lavega et al 2017), Saturn (Sánchez-Lavega et al 2014, 2016a, Venus (Sánchez-Lavega et al 2016b), and Neptune (Hueso et al 2017a). …”
Section: Planetcam Instrumentmentioning
confidence: 99%
“…Differences between the 2016 zonal winds and Cassini winds concentrate in (i) the North Temperate Belt (NTB) with intense zonal winds in 2015 [ Simon et al ., ] and 2016 possibly required for the development of large‐scale disturbances [ Sánchez‐Lavega et al , , ], (ii) the NEB where the presence of large dark projections moving more slowly than the winds makes zonal winds apparently less intense [ Asay‐Davis et al , ; Barrado‐Izagirre et al , ; Choi et al , ], and (iii) the peak of the SEB jet where a wave system partially observed over 2015 may also affect the zonal winds resulting in less intense motions [ Rogers et al , ].…”
Section: Zonal Windsmentioning
confidence: 64%
“…Zonal winds could be measured over different temporal periods without noticeable changes except for a high value of the NTB jet which peaked at 157 ± 3 m s −1 . These high speeds of the NTB jet seem to occur previous to the development of large‐scale convective outbreaks [ Sánchez‐Lavega et al , ] as the one developed in October 2016 [ Sánchez‐Lavega et al , ]. PlanetCam observations of the polar regions at filters not sensitive to methane absorption provide dynamical context to the high‐resolution polar observations of JunoCam [ Orton et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…What came next was even more spectacular— Sánchez‐Lavega et al . [] report the eruption of four extraordinary plumes near Jupiter's fastest eastward jet at 23.9°N, characteristic of another cycle of atmospheric variability in the North Temperate Belt (NTB) [ Sánchez‐Lavega et al , , ]. The October 2016 NTB eruption was remarkable for several reasons: (i) Juno had just arrived in the Jovian system to observe the phenomenon; (ii) four plumes at widely separated longitudes were identified; and (iii) the Earth‐based support campaign was able to provide remarkable temporal coverage even though Jupiter was still relatively close to solar conjunction.…”
Section: Jupiter's Belts In 2016mentioning
confidence: 99%